Grey matter, blue matter. (Economist, 2005)
The article offers a look at the efforts of scientists to replicate elements of the human brain in computer form. The most complex object known to humanity is the human brain--and not only is it complex, but it is the seat of one of the few natural phenomena that science has no purchase on at all, namely consciousness. To try to replicate something that is so poorly understood may therefore seem like hubris. But you have to start somewhere, and IBM and the Ecole Polytechnique Fédérale de Lausanne (EPFL), in Switzerland, propose to start by replicating "in silico ", as the jargon has it, one of the brain's building blocks. In a partnership announced on June 6th, the two organizations said they would be working together to build a simulation of a structure known as a neocortical column on a type of IBM supercomputer that is currently used to study the molecular functioning of genes. If that works, they plan to use future, more powerful computers to link such simulated columns together into something that mimics a brain. In a real brain, a neocortical column is a cylindrical element about a third of a millimeter in diameter and three millimeters long, containing some 10,000 nerve cells. The EPFL's contribution to the Blue Brain Project, as it has inevitably been dubbed, will be to create a digital description of how the columns behave. Its Brain Mind Institute has what is generally regarded as the world's most extensive set of data on the machinations of the neocortex--the columns' natural habitat and the part of the brain responsible for learning, memory, language and complex thought.